2014
DOI: 10.1105/tpc.114.122739
|View full text |Cite
|
Sign up to set email alerts
|

Global Dissection of Alternative Splicing in Paleopolyploid Soybean

Abstract: Alternative splicing (AS) is common in higher eukaryotes and plays an important role in gene posttranscriptional regulation. It has been suggested that AS varies dramatically among species, tissues, and duplicated gene families of different sizes. However, the genomic forces that govern AS variation remain poorly understood. Here, through genome-wide identification of AS events in the soybean (Glycine max) genome using high-throughput RNA sequencing of 28 samples from different developmental stages, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
253
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(309 citation statements)
references
References 102 publications
(158 reference statements)
49
253
4
3
Order By: Relevance
“…The direct transcripts from MIRNAs are generally processed to produce mature miRNAs and thus have been well characterized. Interestingly, the transcripts from 26 of the 48 MIRNAs within introns were detected in 28 mRNA libraries described previously (Shen et al, 2014), as were the splicing patterns of their host PEGs detected in the same libraries that remove these intronic sequences (Supplemental Table 2). Because some of these putative MIRNA transcripts cover the intron-exon junctions of their host PEGs, and some are arranged in opposite orientations to the hosting PEG's transcripts, the coexistence of transcripts from these intronic MIRNAs and respective host PEGs in the same libraries would suggest separate and independent transcription of the PEGs and respective MIRNAs.…”
Section: Distribution Of Mirnas In Terms Of Their Genomic Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct transcripts from MIRNAs are generally processed to produce mature miRNAs and thus have been well characterized. Interestingly, the transcripts from 26 of the 48 MIRNAs within introns were detected in 28 mRNA libraries described previously (Shen et al, 2014), as were the splicing patterns of their host PEGs detected in the same libraries that remove these intronic sequences (Supplemental Table 2). Because some of these putative MIRNA transcripts cover the intron-exon junctions of their host PEGs, and some are arranged in opposite orientations to the hosting PEG's transcripts, the coexistence of transcripts from these intronic MIRNAs and respective host PEGs in the same libraries would suggest separate and independent transcription of the PEGs and respective MIRNAs.…”
Section: Distribution Of Mirnas In Terms Of Their Genomic Environmentmentioning
confidence: 99%
“…To detect the transcripts of MIRNAs embedded in the host PEGs and splicing sites of the host PEGs, RNA-seq data from 28 samples of soybean (Glycine max) tissues at different developmental stages previously generated (Shen et al, 2014) were retrieved and reanalyzed. The RNA-seq reads were uniquely mapped to the soybean reference genome allowing mismatch of a single nucleotide per paired reads using TopHat2 ).…”
Section: Methodsmentioning
confidence: 99%
“…While many studies have identified AS in individual species (Filichkin et al 2010;Li et al 2014;Shen et al 2014;Thatcher et al 2014;Mandadi and Scholthof 2015), there are few reports of conserved AS across multiple plant genomes. Most published studies have focused on identifying conserved AS events between only two species.…”
mentioning
confidence: 99%
“…In a concurrent study, Shen et al (2014) identified AS events in soybean and compared the number of AS events present in genes duplicated by a paleopolyploidy event. They found that the number of AS events was different in the vast majority of duplicate pairs.…”
Section: Discussionmentioning
confidence: 99%